2016
DOI: 10.1007/s00394-016-1334-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in food intake and genetic variability in taste receptors between Czech pregnant women with and without gestational diabetes mellitus

Abstract: Our study showed differences in dietary intake of selected food items between healthy pregnant women and those with GDM and genetic association of bitter taste receptor allele with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…There is evidence that polymorphisms of BTR genes that impair the sensitivity to bitterness may be associated with changes in food intake and dysregulation of blood glucose. For example, women with gestational diabetes mellitus exhibited a lower T2R9 gene (rs3741845) frequency, and consumed more meat, dairy and sweet beverages compared to pregnant women without gestational diabetes mellitus ( 79 ). Similarly, dysfunction of T2R9 due to a single nucleotide polymorphism is associated with higher blood glucose and insulin responses to an oral glucose tolerance test in Amish individuals with and without type 2 diabetes ( 38 ).…”
Section: Clinical Implications Of Targeting Intestinal Btrsmentioning
confidence: 99%
“…There is evidence that polymorphisms of BTR genes that impair the sensitivity to bitterness may be associated with changes in food intake and dysregulation of blood glucose. For example, women with gestational diabetes mellitus exhibited a lower T2R9 gene (rs3741845) frequency, and consumed more meat, dairy and sweet beverages compared to pregnant women without gestational diabetes mellitus ( 79 ). Similarly, dysfunction of T2R9 due to a single nucleotide polymorphism is associated with higher blood glucose and insulin responses to an oral glucose tolerance test in Amish individuals with and without type 2 diabetes ( 38 ).…”
Section: Clinical Implications Of Targeting Intestinal Btrsmentioning
confidence: 99%
“… vitamin and mineral pregnancy dietary intake Mean vitamin C intake was higher in controls than among cases ( p -value: 0.04). Mean calcium intake was higher in controls than among cases ( p -value: 0.01) Bartáková V, et al 2018 [ 43 ] Czech Republic - Europe n:363 cases:293 controls:70 case-control women aged 29–36 years who visited the Diabetes Centre of the University Hospital Brno. Gestational age between 24 and 30 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Three case-control studies, six cohorts and one cross-sectional study found an association between food or meals and the risk of developing GDM. The case-control studies evaluated adherence to dietary acid load (calculated using several nutrient intakes such as phosphorus, protein, calcium, magnesium and potassium) and the mediterranean diet (adherence to vegetables, fruits, legumes, cereals and bread, pasta, rice; fish and seafood; meat, poultry; dairy products; alcohol and ratio MUFAs/SFAs), food consumption and the asociation with GDM risk [ 30 , 43 , 60 ]. Women with higher scores of dietary acid load and a low mediterranean diet score were more likely to have GDM during pregnancy (OR = 9,27; 95% CI: 4.00–21.46) [ 30 , 56 ] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational diabetes mellitus (GDM) is often defined as a disturbance in glucose tolerance first detected during pregnancy. [1][2][3][4][5] The prevalence of GDM has increased steadily, with 14% of pregnancies in USA, 5.7% of pregnancies in Australia, and 5-10% of pregnancies in Asian countries presenting with GDM. In Iran, the prevalence of GDM has been estimated at 3.4% of all annual pregnancies.…”
Section: Introductionmentioning
confidence: 99%